High-capacity terahertz carrier generation using a modified add-drop filter for radio frequency identification - Luangxaysana, Khanthanou; Mitatha, Somsak; Yoshida, Masahiro; Komine, Noriyuki; Yupapin, Preecha (My University, 2012)
A new technique of terahertz (THz) frequency carrier generation for multi-channel radio frequency identification (RFID) use is proposed. The dense wavelength division multiplexing signals can be obtained by using a Gaussian pulse propagating within a modified add-drop filter known as a PANDA ring resonator. The THz device system can be made contributions to the promising applications, especially in highspeed switching, demultiplexing, and wavelength conversion of optical signals, in which the effect of THz control is also required and essential for the potential application to ultra-high speed wireless digital interconnects for computer chips with ultra-high clock rates. In principle, the high-density frequency (wavelength) can be generated and used to form the RFID; moreover, the tiny device system is another advantage, which can be constructed to incorporate the currently used system. The results obtained have shown that higher density and increasing channel capacity can be obtained and are useful for the large demand for RFID applications. © 2012 Society of Photo-Optical Instrumentation Engineers (SPIE).
Keywords: PANDA ring resonator; Pulse modulation; Radio frequency identification carrier; Terahertz technology